2020
DOI: 10.1007/s00415-020-09777-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of incobotulinumtoxinA in post-stroke upper-limb spasticity in Japanese subjects: results from a randomized, double-blind, placebo-controlled study (J-PURE)

Abstract: Background Upper-limb spasticity frequently occurs after stroke and there is a clinical need for more effective therapies. The Phase III J-PURE study assessed the efficacy and safety of incobotulinumtoxinA up to 400 U for post-stroke upper-limb spasticity in Japan. Methods In the 12-week main period (MP) of this double-blind, placebo-controlled study, Japanese subjects with upperlimb spasticity received one injection cycle of incobotulinumtoxinA 400 U, 250 U, or matching placebo. Eligible subjects enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 20 publications
7
28
0
3
Order By: Relevance
“…This pooled analysis of six studies, four of which were randomised, double-blind and placebo-controlled in design, showed that incobotulinumtoxinA significantly reduces pain compared with placebo in adult patients with upper limb spasticity-associated pain. These results confirm the pain-relieving benefits of incobotulinumtoxinA observed in the individual studies [12,14,15,27,34]. In this pooled population of patients with limb spasticity considered suitable for treatment with BoNT-A, approximately 60% of patients experienced pain at baseline.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This pooled analysis of six studies, four of which were randomised, double-blind and placebo-controlled in design, showed that incobotulinumtoxinA significantly reduces pain compared with placebo in adult patients with upper limb spasticity-associated pain. These results confirm the pain-relieving benefits of incobotulinumtoxinA observed in the individual studies [12,14,15,27,34]. In this pooled population of patients with limb spasticity considered suitable for treatment with BoNT-A, approximately 60% of patients experienced pain at baseline.…”
Section: Discussionsupporting
confidence: 81%
“…Analyses were based on pooled results from six prospective, multicentre, Phase 2 or 3 studies of incobotulinumtoxinA (Xeomin ® ; Merz Pharmaceuticals GmbH, Frankfurt, Germany) in the treatment of upper (five studies: MRZ_60201_0307); [12,14,27,34]) and/or lower (one study: [15]) limb muscle spasticity in adults. The studies were part of the clinical development programme for incobotulinumtoxinA and were performed across multiple countries and continents worldwide, including Europe, Canada, USA, Japan, India and Russia.…”
Section: Studies Included In the Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12-week, double-blind, placebo-controlled study shows that active movement improves in the study group that received treatment with botulinum toxin type A. Furthermore, the scale of disability and clinical evaluation according to the examiner′s overall impression show that INCO reduced increased muscle tone, improved functionality, and was well tolerated in Japanese subjects with upper limb spasticity after stroke [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum neurotoxins (BoNTs) have been approved for spasticity treatment in many countries. There is strong evidence that they reduce muscle tone in spasticity (5,6), but it is uncertain whether they are useful in improving functional disabilities of the limbs such as increasing active range of motion (ROM). Spasticity is defined as increased muscle tone as a consequence of upper motor neuron dysfunction or loss.…”
Section: Introductionmentioning
confidence: 99%